Isolation and identification of three new chromones from the leaves of Pimenta dioica with cytotoxic, oestrogenic and anti-oestrogenic effects - Brian J. Doyle; Temitope O. Lawal; Tracie D. Locklear; Lorraina Hernandez; Alice L. Perez; Udeshi Patel; Shitalben Patel; Gail B. Mahady (Pharmaceutical Biology, 2018)
Context: Pimenta dioica (L.) Merr. (Myrtaceae) is used in Costa Rican traditional medicine for women’s health. Our previous work showed that P. dioica extracts were oestrogenic. Objectives: This work identifies phytochemicals from P. dioica that are responsible for the plant’s oestrogen-like activities. Materials and methods: P. dioica leaves were collected in Costa Rica in 2005. Fractions resulting from chromatographic separation of a methanol extract were tested at 50 μg/mL in a competitive oestrogen receptor-binding assay. Active compounds were isolated by HPLC and identified by NMR and MS. Pure compounds were tested at 1 μM in the oestrogen-responsive SEAP reporter gene assay. The effects on cell viability, cytotoxicity and apoptosis were investigated in breast cancer (MCF-7 and SK-BR3) and gastric cancer (AGS and NCI-N87) cell lines using the ApoTox-Glo and Caspase-Glo assays and qPCR. Results: Quercitrin and three new chromones, including a 2-phenoxychromone, 6,8-di-C-methylcapillarisin (1) were isolated and identified. Compound 1 caused a 6.2-fold increase in SEAP expression at 1 μM (p < 0.05). This activity was blocked by the ER antagonist ICI 182,780. Compound 2 caused a 6.0-fold increase in SEAP, inhibited the growth of MCF-7, AGS and NCI-N87 cells (IC50 54.27, 38.13 and 51.22 μg/mL, respectively), and induced apoptosis via caspase 8 and increased the Bax/Bcl-2 mRNA ratio in MCF-7 cells. Compound 3 was anti-oestrogenic in MCF-7 cells. Discussion and conclusions: Compounds from P. dioica have oestrogenic, anti-oestrogenic and cytotoxic effects that may explain the ethnomedical use of this plant.